1998
DOI: 10.1007/bf02688657
|View full text |Cite
|
Sign up to set email alerts
|

Decoding the language of the heart: Developing a physiology of inclusion

Abstract: Constructs such as homeostasis and fight/flight have supported a scientific approach to physiology that has yielded a vast database of obvious heuristic value. Yet in spite of its value, these constructs have tended to create a mind-set that unwittingly supports what this article has labeled a "physiology of exclusion." Reinforced by the philosophy of René Descartes, this perspective has led investigators to focus on isolated or separate animal organisms that are reflexively wired for self-preservation. It has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…One interpretation of the latter finding could be that patients scoring high on intermember group cohesion may feel more at ease and safe in the presence of other group members and therefore gain more from the relaxation exercises, which were often reported to have a positive effect on blood pressure [37, 38, 39, 40]. This interpretation is in agreement with Lynch’s view [41, 42]that feeling safe in the presence of others increases the positive effects of treatment on blood pressure, while feeling uncomfortable in the presence of others leads to negative effects on blood pressure. As an illustration of this effect, our study patients scoring ≥27 on the Bond-M scale showed a pre- to posttreatment improvement of systolic blood pressure (mean systolic blood pressure, 138 and 133, respectively; Cohen’s d = 0.22), whereas patients scoring <27 on this scale showed a deterioration of systolic blood pressure (mean systolic blood pressure, 144 and 150, respectively; Cohen’s d = –0.55).…”
Section: Discussionsupporting
confidence: 81%
“…One interpretation of the latter finding could be that patients scoring high on intermember group cohesion may feel more at ease and safe in the presence of other group members and therefore gain more from the relaxation exercises, which were often reported to have a positive effect on blood pressure [37, 38, 39, 40]. This interpretation is in agreement with Lynch’s view [41, 42]that feeling safe in the presence of others increases the positive effects of treatment on blood pressure, while feeling uncomfortable in the presence of others leads to negative effects on blood pressure. As an illustration of this effect, our study patients scoring ≥27 on the Bond-M scale showed a pre- to posttreatment improvement of systolic blood pressure (mean systolic blood pressure, 138 and 133, respectively; Cohen’s d = 0.22), whereas patients scoring <27 on this scale showed a deterioration of systolic blood pressure (mean systolic blood pressure, 144 and 150, respectively; Cohen’s d = –0.55).…”
Section: Discussionsupporting
confidence: 81%
“…As Dunbar's early work indicated, researchers have long recognized that life events involving separation and loss are powerful in producing distress and dysfunction in the human organism. James Lynch, in his The Broken Heart : The Medical Consequences of Loneliness ( 1977 ) , and later publications (Lynch, 1998 ;Lynch & Convey, 1979 ) highlighted the importance of separation, loss, and loneliness in triggering cardiovascular illness and other forms of medical and psychiatric illness. Both morbidity and mortality increase following signi fi cant losses.…”
Section: Stressful Life Events and Healthmentioning
confidence: 99%
“…The second prong, ably summarized by Kira (2001), indicated that there was a gradation from A Case for More Survival Strategies PTSD emphasizes fight and flight responses in its fourth criterion. Lynch (1998) noted, however, that for PTSD to see humans as hard-wired only for fight and flight was too restrictive. It ignored other strategies, which dealt with, say, abandonment, loss, and need to save others' lives.…”
Section: Paul Valentmentioning
confidence: 99%